"To Prevent Further Despoliation" A History of the Arizona Antiquities Act. Issue 3 (3rd July 2017) - Grindell, Beth
Abstract : For 90 years, the Arizona Antiquities Act has both shaped and responded to the development of archaeology in the state. The earliest law, passed in 1927, met a severe legal challenge but set a precedent for a state role in controlling and preserving archaeology on state lands. Over the next six decades, there were three major amendments (1960, 1983, 1990) and two smaller ones (1981, 1998). The article summarizes the changes and several failed attempts to amend the laws and reviews the difficulties and occasional successes in prosecuting vandalism and looting of archaeology on state lands. Despite the legislation's occasionally convoluted history, it has contributed enormously to our understanding of Arizona's rich history.